Macroeconomic effects of the Covid-19 Pandemic in Germany and the European Monetary Union and economic policy reactions - Hansjörg Herr; Zeynep Mualla Nettekoven (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
The Covid-19 pandemic hitting the world in 2020 also caused a high death toll in Germany and in the European Monetary Union (EMU) at large. The health crisis worldwide and the precautions against Covid-19 rapidly induced a demand and supply recession simultaneously. The Covid-19 crisis was marked as the worst crisis since the Great Depression of the 1930s. It hit the EMU in an unfortunate moment, when economic growth was already low before the Covid-19 crisis started. The effects of the Great Financial Crisis and Great Recession 2008/2009 were not overcome at the beginning of the Covid-19 recession. Mega-expansionary monetary policy was still in place stimulating bubbles in stock and real estate markets in an overall constellation of partly very high levels of private and public debt. Macroeconomic policies in form of expansionary monetary policy, large-scale fiscal stimuli, and public guarantees, in Germany and the EMU smoothed the disastrous economic and social effects of the pandemic. Overall, the stabilisation policy during the Covid-19 pandemic in Germany was successful and prevented escalating inequalities. But the pandemic intensified long-lasting problems which have to be solved in the future. Public debt quotas cannot increase permanently without leading to an economically fragile situation. It also shows the need for a fiscal union in the EMU as an equal partner for the European Central Bank (ECB). In early 2022, the ECB is in a difficult situation. Price shocks drove the inflation rate up, but restrictive monetary policy as a response to such shocks slowdown growth and lead to unemployment.
Keywords: E61; F62; I18; 330; Covid-19 crisis; Germany; EU; fiscal policy; monetary policy